Analysis of Discipline, Organizational Commitment, Work Environment and Their Effect on Employee Performance PT. Adhiyasa Bangkinang - Zamhir Basem; Zulher; Muhammad Yusril; Novia Dwi Pangestika (Global Writing Academica Researching and Publishing, 2022)
Organizational performance is determined by the work of all human resources in the organization, both leadership and workers. There are so many factors that can affect human resources in carrying out their performance. There are factors that come from within HR itself and from outside itself. Many factors can improve employee performance, including creating a conducive work environment, work discipline and high work commitment. This research was conducted at PT. Adhiyasa Bangkinang, Kampar Regency. The purpose of this study is to see and analyze the effect of work discipline, organizational commitment and work environment variables on employee performance either partially or simultaneously. The research population was all employees, totaling 31 people and all of them were used as samples. The data used are primary data and secondary data obtained from questionnaires, interviews and documentation. Data analysis was carried out with multiple linear regression and hypothesis testing was carried out through t test and F test with 5% alpha. The results of this study conclude that work discipline, organizational commitment and work environment have a significant effect on employee performance either partially or simultaneously.